2021
DOI: 10.2174/1874312902115010001
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Literacy, Patient Activation, and Functional Capacity in Individuals with Rheumatoid Arthritis

Abstract: Objectives: To describe health literacy, patient activation, and functional capacity in individuals with rheumatoid arthritis and to evaluate the associations of health literacy and activation level with functional capacity. Methods: A cross-sectional study involving patients with rheumatoid arthritis was carried out at the rheumatology service of a teaching hospital. Health literacy was assessed by applying the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
5
1
1
Order By: Relevance
“…While Oliveira et al . [ 18 ] observed the relationship between functional disability and patient activation, our study findings did not support this relationship.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…While Oliveira et al . [ 18 ] observed the relationship between functional disability and patient activation, our study findings did not support this relationship.…”
Section: Discussioncontrasting
confidence: 93%
“…Participants in our study had lower average PAM scores than those reported by Oliveira et al . [ 18 ] in a Brazilian study. While Oliveira et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Four other studies from the United Kingdom, Italy, Singapore, Brazil and Iran only reported mean PAM without categorization. 13,[32][33][34][35][36] Lofland et al assessed the PAM in patients who initiated biologics and the impact of adequate shared decision-making. 37 A higher mean PAM was observed in patients who had adequate shared decisionmaking (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Current research on health literacy levels in patients with rheumatic diseases has focused on systemic lupus erythematosus and rheumatoid arthritis (26,27). The findings show an association between patient health literacy and disease activity, medication adherence, functional status, and additional health outcomes (28)(29)(30). We found only one study related to SSc patient health literacy, which, unlike traditional health literacy studies, was an assessment of e-health literacy, focusing on assessing patients' use of e-health resources and need for web-based support (31).…”
Section: Introductionmentioning
confidence: 99%